Social media use, personality characteristics, and social isolation among young adults in the United States. (1st April 2018) - Whaite, Erin O.; Shensa, Ariel; Sidani, Jaime E.; Colditz, Jason B.; Primack, Brian A.
Abstract: Although increased social media use (SMU) has been linearly associated with increased real-life social isolation (SI), it is unknown whether these associations differ by personality characteristics. With a nationally-representative sample of 1768 U.S. young adults aged 19–32, we assessed SI using a 4-item Patient-Reported Outcomes Measurement Information System scale, and personality using the 10-item Big Five Inventory. Using ordered logistic regression, we evaluated multivariable associations between SMU, personality characteristics, and SI. Extraversion and agreeableness were associated with lower odds of SI, while neuroticism was associated with higher odds. A significant interaction term demonstrated that the association between SMU and SI differed by conscientiousness. Among those with low conscientiousness, compared with the lowest quartile of SMU, those in the highest quartile had more than three times the odds (AOR = 3.20, 95% CI = 1.99, 5.15) for increased SI, but there was no significant association among the high conscientiousness group. Interaction terms between SMU and the other four personality characteristics were not significant. Conscientious individuals may approach social media in a way that helps maintain good face-to-face social interactions, reducing perceived SI. Highlights: We studied a nationally-representative sample of young adults ages 19–32. Extraversion and agreeableness were associated with lower odds of social isolation. Neuroticism was associated with higher odds of social isolation (OR = 3.08). For low conscientiousness only, social media use was associated with social isolation.